Contextual and individual factors associated with dissatisfaction with public emergency health services in Brazil, 2011-2012 - Rafaela Soares Rech; Fernando Neves Hugo; Jessye Melgarejo do Amaral Giordani; Lúcia Gimenes Passero; Juliana Balbinot Hilgert (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
The Brazilian network of emergency care, in recent years, has shown significant progress. The objective was to evaluate contextual and individual factors associated with the satisfaction with public emergency health services. This was a cross-sectional multilevel study carried out between June 2011 and January 2012. Data were collected via telephone at the ombudsman's office of the Brazilian Unified National Health System (SUS). Telephone numbers were randomly selected from a telephone company database. Health services, socioeconomic, and individual demographic variables were evaluated, in addition to information about the municipalities. The outcome variable was dissatisfaction with public emergency health services in Brazil. Multilevel logistic regression was performed and 7,027 individuals from 61 municipalities answered the survey. The prevalence of perceived dissatisfaction was 48.1% (95%CI: 46.9-49.3). Variables that remained significantly associated with the outcome are: age up to 20 years, 16 or more years of education, lives in the Central region, non-resolved demands, longer waiting times, and accessing emergency in a primary care service. Prevalence of a perceived dissatisfaction is predominantly associated with care's waiting time and the length needed to resolve the demand.